2022
DOI: 10.3390/ijerph192215350
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Post-COVID-19 Musculoskeletal Sequelae in Geriatric Patients: A Case Series Study

Abstract: The musculoskeletal system is affected in over 40% of patients with Coronavirus disease 2019 (COVID-19). There is an increased need for post-acute rehabilitation after COVID-19, especially in elderly people with underlying health problems. The aim of this study was to evaluate the benefits of an early and goal-orientated rehabilitation program using combined approaches, robotic medical devices together with other rehabilitation techniques and therapies, in elderly people after acute COVID-19. Ninety-one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…While current studies confirm the improvement of quadriceps strength after rehabilitation [ 36 , 91 ], the results of the change of hand force after rehabilitation are inconsistent. Significant improvements were observed in some studies [ 34 , 36 ], whereas other studies [ 91 , 92 ] demonstrated only trends comparable with our results. Muscle fatigue of handgrip is part of fatigability.…”
Section: Discussionsupporting
confidence: 85%
“…While current studies confirm the improvement of quadriceps strength after rehabilitation [ 36 , 91 ], the results of the change of hand force after rehabilitation are inconsistent. Significant improvements were observed in some studies [ 34 , 36 ], whereas other studies [ 91 , 92 ] demonstrated only trends comparable with our results. Muscle fatigue of handgrip is part of fatigability.…”
Section: Discussionsupporting
confidence: 85%
“…Their findings demonstrated notable enhancements in the FIM total score from admission to discharge. Cevei et al [ 26 ] conducted a clinical trial with six elderly patients (all over 80 years old) using LOKOMAT for gait robotic rehabilitation over a span of 4 weeks. With an average hospital stay of 17 days and no ICU admissions, significant improvements were observed in the FIM total score but not in the BI, attributing the results to the limited sample size and the advanced age of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only three studies have examined the effectiveness of robotic rehabilitation therapies in COVID-19 patients. These studies targeted lower limb robotic rehabilitation using LOKOMAT (Hocoma, Volketswil, Switzerland) [ 26 ], ANDAGO (Hocoma, Volketswil, Switzerland) [ 27 ], and LUNA EMG (EGZOTech, Gliwice, Poland) [ 28 ], thereby neglecting hand rehabilitation as a specific focus. Thus, our research aims to fill this knowledge gap by offering novel insights into the effectiveness of exoskeleton-based hand-assisted rehabilitation for COVID-19 patients and its potential impact on their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology is multifactorial. Age-related decline, chronic diseases, presbyphagia, qualitative and quantitative muscle tissue impairment, hormonal changes and cellular metabolism (the imbalance between protein synthesis and degradation) are some of the factors involved in the occurrence of sarcopenia [4,5]. The loss of muscle mass and strength associated with the ageing process defines primary sarcopenia, which may contribute to a decrease in mobility, balance, coordination and the ability to perform activities of daily living [6].…”
Section: Introductionmentioning
confidence: 99%